Contribuição ao controle de máquinas de vibração eletrodinâmicas - Della Flora, Leandro (2009)
This work presents contributions to the sinusoidal acceleration control of electrodynamic shakers applied in vibration testing. Considering the importance of sine tests to identify critical frequencies of operation and to determine mechanical weakness in the specified performance of specimens, vibration controllers are designed to reproduce the amplitude and the frequency of the reference acceleration specifically at the interface between the shaker and the structure under test. Two distinct approaches are considered to solve the control problem: time domain control, where the acceleration instantaneous value is adjusted to track the sinusoidal reference, and frequency domain control, in which only the amplitude or the root mean square value of the acceleration is compensated to follow the reference magnitude. The solutions developed based on these two different approaches are implemented in a digital control platform and experimentally evaluated. The development of vibration controllers is complemented by contributions to the study of the shaker dynamic model, as well as to the instrumentation applied to measure and feedback the acceleration and to the voltage control of switching-mode power amplifiers designed to drive the shaker. Regarding the vibration machine dynamic model, a method is proposed to experimentally identify the mechanical parameters of a two degrees of freedom system that represents the suspension resonance and the finite armature stiffness of the electrodynamic shaker. A procedure is developed to design and implement charge mode preamplifiers and signal conditioning circuits for piezoelectric accelerometers. A robust model reference adaptive algorithm is applied to control the output voltage of an industrial switching-mode power amplifier. The experimental analysis of the adaptive controller considers not only the improvements on the power amplifier performance, but also the of impact over the behavior of a commercial digital vibration control system.